EDITORIAL - Vongurai, Rawin (Scholar: Human Sciences, 2025)
The Scholar: Human Sciences, a journal encompassing the fields of humanities and social sciences, has earned acclaim in the Thailand Citation Index (TCI) as a prominent publication since 2015. It currently holds the esteemed TCI: TIER1 classification. We take great pride in presenting the latest issue, which features a collection of manuscripts that have undergone rigorous evaluation. Each submission has been meticulously reviewed through a blinded review process by three specialized reviewers from different institutions, both internal and external to the authors. This peer-reviewed accreditation ensures the scholarly quality and integrity of the published articles. This issue covers thirty-one articles. The first article titled “Elements Influencing College Graduate Students’ Satisfaction and Behavioral Intention to Employ MOOC in Chengdu, China” examined the factors that affect learners’ behavioral intention and satisfaction with MOOC learning in Chengdu, China. The second article titled “Investigation on Student Immersion and Buying Intent on Chengdu Live Platforms” focused on the factors that impact the immersion and purchase intentions of university students in Chengdu on live streaming platforms. The third article titled “Developing Business Students’ Learning Performance in Chongqing, China” identified effective strategies for enhancing students’ learning outcomes. The fourth article titled “Factors Influencing Students’ Intention to Use E-Learning in Zhanjiang, China” examined the factors influencing students’ behavioral intention to use e-learning in Zhanjiang, China. The fifth articled titled “Exploring What Drives Undergraduates at Xihua University in Chengdu to Stick with Short Video Apps” proposed a causal relationship among information sharing, information seeking, social interaction, entertainment, facilitating condition, and satisfaction impacting continuance intention. The sixth article titled “Uncovering the Key Factors Behind Junior College Students’ Satisfaction and Commitment to E-Learning in Jiangxi, China” examines the factors influencing junior college students’ satisfaction and continued intention to engage in e-learning in Jiangxi, China. The seventh article titled “Developing Teachers’ Job Satisfaction in Jilin, China” proposed strategies for improvement to enhance the quality of education and promote educational reform. The eighth article titled “An Empirical Study on How Strategic Plan Interventions Boost Teachers’ Job Satisfaction at Zhanjiang University of Science and Technology in Guangdong Province” explored the impact of school culture, resources, workload, training, and development on teachers’ job satisfaction in private undergraduate universities and identifies significant differences between variables. The ninth article titled “Understanding the Drivers of College Students’ Attitudes and Intentions Towards Online Shopping in China” explored the factors that influence the purchase intention of online shopping among college students in Zhanjiang, China. The tenth article titled “Enhancing Learning Satisfaction in Technology-Driven Education: A Case Study from a Public University in Chongqing, China” explained perceived learning effectiveness, perceived enjoyment, perceived usefulness, and information technology emerged as crucial predictors and antecedents of learning satisfaction. The eleventh article titled “Exploring the Drivers of Employee Creativity in Chengdu’s State-Owned Creative Enterprises in Chengdu, China” aimed to investigate the key factors that affect the development of employee creativity in state-owned creative companies in Chengdu, Sichuan, China. The twelfth article titled “Impacting Factors of College Students’ Satisfaction with Leadership Education in Jiaxing, China” explored the factors influencing students’ satisfaction with leadership education in a public university in Jiaxing, China. The thirteenth article titled “Enhancing Online Meeting Adoption Among Chengdu’s Youth” identified the determinants of young people’s satisfaction, perceived usefulness, and continued intention to use online meetings in Chengdu, China. The fourteenth article titled “Exploring the Influences on Leadership Skills Development Among Dance Students at a Normal University in Lanzhou, China” provided strategic planning and a foundation for future interventions to enhance students’ leadership competencies. The fifteenth article titled “Key Factors of Undergraduate Satisfaction and Continued Use of Mobile Shopping Apps in Yibin, China” examined the significant impact of key factors of mobile shopping applications on satisfaction and intention to reuse among university students in Yibin, China. The sixteenth article titled “Exploring the Link Between Product Innovation and Firm Performance: Empirical Insights from Energy Enterprises in Yunnan, China” constructed a comprehensive theoretical framework to test the influence of key resource factors within the frameworks of the Resource-Based View and Customer Relationship Management theories on product innovation and firm performance. The seventeenth article titled “Unveiling the Influencers of Online Shopping Intentions: A Case Study of Public University Students in Chengdu, China” investigated the determinants influencing students’ inclination to online shopping at a public university in Chengdu, China. The eighteenth article titled “Key Influencers of Virtual Community Knowledge-Sharing Among Chengdu University Students” aimed to investigate the key influencers that significantly impact the willingness of college students to share knowledge using virtual communities in four universities in Chengdu, Sichuan. The nineteenth article titled “Key Factors Shaping Transformational Leadership Training for Student Cadres: A Case Study from a Public Normal University in Chengdu, China” has demonstrated the ability of college student cadres to acquire leadership and comprehensive qualities through the growth of transformational leadership, which has made a significant contribution. The twentieth article titled “Key Factors Influencing Customer Satisfaction and Repurchase Intentions on Online Shopping Platforms in Chengdu, China” investigate the key factors that substantially impact online shopping satisfaction and repurchase intention of three majors at a university in Chengdu, China. The twenty-first article titled “An Investigation on Key Factors Influencing Consumers’ Green Purchase Behavior in Zhengzhou, China” identified and analyzes the factors influencing consumers’ green purchase behavior in Zhengzhou, China. The twenty-second article titled “Key Drivers of Satisfaction and Adoption Intentions for E-Government Among Chengdu’s Government Employees” investigated the crucial elements that significantly impact the intent to utilize E-government services among employees within government departments across three distinct regions in Chengdu, China. The twenty-third article titled “Key Factors Shaping Undergraduate Attitudes and Purchase Intentions for Live-Stream Shopping: A Study in Mianyang, China” aimed to study the factors influencing the Live-stream Shopping Cognitive attitudes and purchase intentions of undergraduate students in Mianyang. The twenty-fourth article titled “Exploring Factors Shaping Patients’ Intentions to Adopt Cancer Management Apps: An Extended UTAUT Approach” aimed to identify the determinants of cancer patients’ behavioral intention to use cancer management applications based on the Extended Unified Theory of Acceptance and Use of Technology Model and other expanded variables. The twenty-fifth article titled “Key Influencers of Intention to Use toward Internet of Things Devices for Residents in Hangzhou, China” study investigated factors affecting Hangzhou residents’ intention to use IoT devices. The twenty-sixth article titled “Key Factors Shaping Vocational College Students’ Perceived Usefulness and Behavioral Intentions to Adopt Internet of Things (IoT) Technology in Sichuan, China” aimed to study which factors significantly impact students’ behavioral intention and perceived usefulness in higher vocational colleges in Sichuan, China when using the Internet of Things (IoT). The twenty-seventh article titled “Key Factors Affecting Junior College Students’ Satisfaction and Loyalty Towards a Social Networking Services Platform in Chengdu, China” aims to research the critical factors impacting junior college students’ satisfaction and user loyalty when using a social networking platform. The twenty-eighth article titled “An Empirical Study of Undergraduate Satisfaction and Adoption Intentions of Artificial Intelligence in Chengdu, China” aimed to investigate the important factors impacting the satisfaction and intention to use Artificial Intelligence of Undergraduates in Chengdu, China. The twenty-ninth article titled “Key Drivers of Student Satisfaction in E-Learning: A Case Study of Higher Education at a Public University in Harbin, China” aimed to help school administrators address questions about E-learning and analyze the factors affecting student satisfaction with E-learning courses at a public university in Harbin, China. The thirtieth article titled “Factors Impacting on Undergraduate Students’ Continuance Intention to Use Shiyibao Intelligent Translation Practice and Teaching Platform: A Case Study of a Private University in Guangdong, China” explored the factors influencing the continuance intention of undergraduate students to use the Shiyibao Intelligent Translation Practice and Teaching Platform in a private university in Guangdong, China. The thirty-first article titled “The Effectiveness of Electronic Cigarette on Smoking Cessation in Adult Smokers: A Systematic review and Meta-analysis” examined the effect size of e-cigarettes on smoking cessation in adult smokers with subgroups analysis based on their intention to quit.